Singlet fission materials for improved solar cells - Soh, Jing Siang (Nanyang Technological University, 2021)
Singlet fission is one of the mechanisms being explored to improve the efficiency of solar cells. High energy photons greater than the bandgap cannot be absorbed by the solar cell and the energy would be lost as heat. Singlet fission aims to tackles this by splitting the high energy photon into two lower energy photons, which can be captured by the solar cell. A five-step scheme is devised for synthesising the target material and the report documents the procedure and results of the synthesis process.